Obtenção e caracterização de levedura recombinante com elevada tolerância a etanol por engenharia evolutiva - Sandri, Juliana Passamani (Universidade Federal de São Carlos, 2019)
The utilization of the hemicellulosic fraction of the biomass is important for the economic viability of the industrial production process for second generation bioethanol. Wild strains of Saccharomyces cerevisiae do not metabolize xylose, but there are recombinant strains of this yeast which are capable of efficiently assimilating this sugar under fermentative conditions are available. However, the implementation of an industrial process for the production of 2G ethanol using recombinant strains depends on the development of fermentation strategies suitable for obtaining ethanol at high concentrations from concentrated hemicellulose hydrolysates containing inhibitor compounds. The objective of this study was to use Evolutionary Engineering techniques to adapt the genetically modified strain of S. cerevisiae MDS 130, under fermentative conditions, to a culture medium containing detoxified hemicellulose (DH) hydrolysate and ethanol concentrations higher than 50 g.L-1. The chosen experimental strategy comprised 3 mains steps. In Step 1, the parental lineage was characterized in relation to its tolerance towards ethanol and inhibitors. In Step 2, the Adaptive Evolution experiments were performed using the methodology of successive transfers to media gradually enriched with ethanol and DH. In Step 3, the characterization of the evolved strain was performed in experiments which were similar to those carried out in Step 1. The experiments were followed by the loss of mass associated with CO2 release. The suspension obtained at the end of each fermentation was characterized in terms of optical density (600 nm) and cell viability. The concentrations of sugars and products present in the filtered samples were determined by high performance liquid chromatography. The results of characterization of the MDS 130 parent strain showed 60 and 50% reduction in ethanol productivity when it was cultured in DH formulated medium and in YPX medium (yeast extract, peptone and xylose) supplemented with 40 g.L-1 of ethanol, respectively. After 4 months and 200 generations, the Adaptive Evolution experiments were completed. The obtained evolved population presented better tolerance to ethanol and inhibitors, maintaining final viability of 80% in media formulated with DH only and containing up to 70 g.L-1 of ethanol. In the characterization experiments, evolved cells showed superior performance in all evaluated aspects. Values of yield, productivity and viability of 0.42 g.g-1; 0.11 g.L-1.h-1 e 90%, respectively, were achieved in cultivation using YPX medium supplemented with 60 g.L-1 of initial ethanol OD600 of 0.1. For initial OD600 3 a productivity as high as 3.18 g.L-1.h-1 from xylose 120 g.L-1, which corresponds to 3-fold the value observed with the parental strain at the same condition. The ethanol tolerance was accessed by incubating the suspensions of parental or evolved cells in the presence of 60 g.L-1. The evolved strain presented high viability up to 60 hours of incubation, while the parental strain suffered from intense viability loss after 20 hours. Thus, in addition to obtaining a strain that is more suitable for industrial fermentations, the present work contributed to the development of an Adaptive Evolution methodology that is easy to apply and follow, allowing the maintenance of fermentative conditions in each batch.
Keywords: Levedura recombinante; Tolerância à etanol; Hidrolisado de hemicelulose; Evolução adaptativa; Recombinant yeast; Ethanol tolerance; Hemicellulose hydrolysate; Adaptive evolution; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA